(untitled) (Lex localis - Journal of Local Self-Government, 2024)
Homeowner associations play a pivotal role in neighbourhood autonomy across the globe. However, compared to homeowner associations in Western countries, the number of neighbourhood autonomous organizations in mainland China, known as owners’ committees, has not experienced exponential growth in the past twenty years. The study examines the election process of owners’ committees by analysing a case study of a new owners’ committee election in X neighbourhood, G city, and aims to derive implications for the election of owners’ committees, considering the distinct challenges they face which include not only the typical collective action dilemma experienced by homeowners in Western countries and regions but also the need to coordinate and strike a balance between state powers and market forces. The findings reveal that the election process of the owners’ committee achieved full-coverage institutional norms by adhering to the guidance of party-building, auditing the qualifications of owners, and strengthening public opinion supervision. It also realised all round owners’ mobilisation through stimulating democratic awareness and community consciousness.